Improving Service Quality towards Consumer Satisfaction on Gojek Transportation Services Using the Importance Perfomance Analysis (IPA) Method - Paris Johannes Ginting; Fendi Wijaya; Calvin Jung (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Gojek is a social-minded company that is leading the online-based transportation industry revolution that can be accessed through an application on a smartphone. Gojek also provides various other services such as GoRide, GoCar, GoFood, GoMart, GoBox, and GoSend. There are various kinds of services provided by Gojek which are expected to be able to maintain and improve service quality. The purpose of this study was to determine the level of satisfaction of Universitas Prima Indonesia students with gojek online transportation services. This type of research is a research using survey method. The minimum number of samples that must be taken is 60 people so that the sample can represent the total population. This research uses importance performance analysis (IPA). Importance performance analysis (IPA) is a method used to measure the level of service satisfaction that is included in the quadrants on the importance performance matrix map. The results of the study show that the service quality and facilities provided by Gojek exceed the expected expectations and are sufficient to consumer satisfaction hearts because the services provided by Gojek can be carried out well by Gojek drivers to consumers and the application made by Gojek is very easy to use.